Gallium Nitride-enabled High Frequency and High Efficiency Power Conversion (Integrated Circuits and Systems,, 2018)
This book demonstrates to readers why Gallium Nitride (GaN) transistors have a superior performance as compared to the already mature Silicon technology. The new GaN-based transistors here described enable both high frequency and high efficiency power conversion, leading to smaller and more efficient power systems. Coverage includes i) GaN substrates and device physics; ii) innovative GaN -transistors structure (lateral and vertical); iii) reliability and robustness of GaN-power transistors; iv) impact of parasitic on GaN based power conversion, v) new power converter architectures and vi) GaN in switched mode power conversion. Provides single-source reference to Gallium Nitride (GaN)-based technologies, from the material level to circuit level, both for power conversions architectures and switched mode power amplifiers; Demonstrates how GaN is a superior technology for switching devices, enabling both high frequency, high efficiency and lower cost power conversion; Enables design of smaller, cheaper and more efficient power supplies.